Benefits and Challenges of Implementing Integrated Interventions of Child Development and Nutrition: Exploring the Benefits and Challenges of Integrated Interventions for Child Development and Nutrition (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Bad nutrition (substandard food quantity andor consistency resulting in under- or over-nutrition) and the lack of resources for early learning contribute to the loss of growth capacity and life-long health and economic inequalities among millions of children under 5 years of age. Healthy infant growth andor nutritional status has been correlated with single-sector measures reflecting either early child development (ECD) or diet, and guidelines generally call for the creation and testing of comprehensive strategies. In addition to the evidence for best practise and benefit-cost, we examined the theoretical and realistic advantages and difficulties of incorporating integrated nutrition and ECD approaches and found that the clear theoretical argument for integration is more complex than the issues answered by the empirical evidence released. Further study is required, for example, to 1) address concerns regarding how integrated messaging impacts the characteristics of caregivers such as well-being, awareness and attitudes and how they influence early child feeding and growth outcomes 2) consider demographic and dietary conditions in which integrated approaches are helpful and 3) investigate how various mechanisms of implementation are helpful.